Pengaruh Pengalaman Pengenalan Lapangan Persekolahan (PLP) bagi Mahasiswa dan Persepsi Pendidikan Profesi Guru (PPG) terhadap Minat Menjadi Guru - Siti Taufiqurrohmah; Wida Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
Student interest in becoming a teacher remains a major challenge in preparing prospective professional teachers, especially amidst increasingly complex changes and demands in education. This study aims to analyze the influence of the School Field Introduction (PLP) experience and perceptions of the Teacher Professional Education (PPG) program on student interest in becoming a teacher. This study used a quantitative approach with a multiple linear regression method. The population in this study were all students of the Economics Education Study Program at Surabaya State University, intake 2020–2022, with a sample of 150 students selected purposively. Data collection was conducted using a questionnaire instrument distributed online via Google Form. The collected data were analyzed using multiple linear regression tests to examine the partial and simultaneous effects of the independent variables on the dependent variable. The results of the analysis indicate that partially, the PLP experience does not have a significant effect on interest in becoming a teacher. Conversely, student perceptions of the PPG program show a positive and significant effect on interest in becoming a teacher. Simultaneously, the PLP experience and PPG perceptions significantly influence student interest in becoming a teacher. These findings indicate that perceptions of PPG have a more dominant contribution in shaping interest in becoming a teacher than PLP experience. Therefore, it is crucial for educational institutions to improve the understanding and quality of PPG program implementation to encourage students' interest in pursuing a career as teachers. This research provides practical implications for curriculum designers and teacher education program managers to place greater emphasis on students' perceptions and readiness for PPG in order to produce professional and highly motivated teachers.